The initial maturation status of marmoset testicular tissues has an impact on germ cell maintenance and somatic cell response in tissue fragment culture. (1st April 2020) - Heckmann, L; Langenstroth-Röwer, D; Wistuba, J; Portela, J M D; van Pelt, A M M; Redmann, K; Stukenborg, J B; Schlatt, S; Neuhaus, N
Abstract: Successful in vitro spermatogenesis was reported using immature mouse testicular tissues in a fragment culture approach, raising hopes that this method could also be applied for fertility preservation in humans. Although maintaining immature human testicular tissue fragments in culture is feasible for an extended period, it remains unknown whether germ cell survival and the somatic cell response depend on the differentiation status of tissue. Employing the marmoset monkey ( Callithrix jacchus ), we aimed to assess whether the maturation status of prepubertal and peri-/pubertal testicular tissues influence the outcome of testis fragment culture. Testicular tissue fragments from 4- and 8-month-old ( n  = 3, each) marmosets were cultured and evaluated after 0, 7, 14, 28 and 42 days. Immunohistochemistry was performed for identification and quantification of germ cells (melanoma-associated antigen 4) and Sertoli cell maturation status (anti-Müllerian hormone: AMH). During testis fragment culture, spermatogonial numbers were significantly reduced ( P  < 0.05) in the 4- but not 8-month-old monkeys, at Day 0 versus Day 42 of culture. Moreover, while Sertoli cells from 4-month-old monkeys maintained an immature phenotype (i.e. AMH expression) during culture, AMH expression was regained in two of the 8-month-old monkeys. Interestingly, progression of differentiation to later meiotic stage was solely observed in one 8-month-old marmoset, which was at an intermediate state regarding germ cell content, with gonocytes as well as spermatocytes present, as well as Sertoli cell maturation status. Although species-specific differences might influence the outcome of testis fragment experiments in vitro, our study demonstrated that the developmental status of the testicular tissues needs to be considered as it seems to be decisive for germ cell maintenance, somatic cell response and possibly the differentiation potential.